Performance evaluation method for ceramic material for internal insulation of high-voltage equipment
Through the performance evaluation method of ceramic materials for insulation in high-voltage equipment, the mass loss, volume resistivity temperature stability, surface charge accumulation and flashover performance of ceramic materials are comprehensively evaluated, and the high-voltage and high-voltage insulation properties of ceramic materials are solved. Due to insufficient insulation performance in the edge surface under high temperature conditions, high-performance ceramic materials suitable for high-voltage equipment are selected.
Patent Information
- Application Number
- CN202411512448.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-11
AI Technical Summary
In existing high-voltage DC electrical equipment, epoxy resin composite insulating materials exhibit insufficient insulation performance along the plane under high voltage and high temperature conditions, resulting in unbalanced electric field strength and reduced flashover voltage.
A method for performance evaluation of ceramic materials for insulation in high-voltage equipment is adopted, and comprehensive evaluation is carried out through mass loss characteristics evaluation, volume resistivity changes with temperature, surface charge accumulation characteristics evaluation under temperature gradient, and surface flashover characteristics evaluation under temperature gradient. Properties of ceramic materials.
Through this method, the performance of ceramic materials under high pressure and high temperature conditions can be effectively evaluated, and ceramic materials with high surface insulation strength and strong compatibility with SF6 gas can be selected to improve the equipment's edge insulation performance and long-term stability.
Smart Images

Figure CN119414115A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-voltage equipment performance testing, and in particular relates to a method for evaluating the performance of ceramic materials used for insulation in high-voltage equipment. Background Art
[0002] At present, composite insulating materials with epoxy resin as the matrix and doped with alumina particles are widely used in SF6 gas insulated DC transmission and transformation equipment. Compared with the insulation strength of SF6 gas, the surface insulation strength of epoxy resin composite insulators is lower, so the gas-solid interface between the insulator and SF6 is the weak point of insulation in the equipment. With the increase of voltage level and transmission capacity of DC transmission system, the electrical, thermal and mechanical working stresses inside the equipment gradually increase, and the surface insulation performance of epoxy resin composite insulating materials has not shown satisfactory results. First, under the temperature gradient, the surface field strength of epoxy resin composite insulating materials transfers to the low-voltage side, resulting in a significant increase in the field strength on the low-voltage side, which is very unfavorable to the surface insulation performance of the insulation structure, and this phenomenon will lead to a significant reduction in the surface flashover voltage. Secondly, the surface charge accumulation phenomenon of epoxy resin composite insulating materials in the DC electric field and the molecular decomposition and performance degradation of organic polymers under long-term thermal action are all important problems faced by epoxy resin composite insulating materials in high-voltage DC electrical equipment.
[0003] Ceramic materials, as an insulating material with high thermal conductivity, high mechanical strength and high durability, have been widely used in power systems. However, traditional ceramic materials may be difficult to be compatible with strong electric field conditions and SF6 gas environment for a long time, and cannot be directly used in the design and manufacture of internal support insulators of pure SF6 gas insulated UHV DC wall bushings.
[0004] Therefore, a performance evaluation method for ceramic materials used for internal insulation of high-voltage equipment is urgently needed to explore new insulating materials that can effectively improve the long-term surface insulation performance of SF6 gas-insulated high-voltage DC electrical equipment. Through a comprehensive evaluation of the performance of ceramic materials used for internal insulation, it is convenient to find a high-performance ceramic insulation material formulation system in combination with actual working conditions, and select a ceramic basic material system with high surface insulation strength and strong compatibility with SF6 gas from a wide variety of high-performance ceramic material formulation systems with greatly different insulation properties. A comprehensive performance evaluation is also conducted from the perspectives of material corrosion resistance, temperature stability of volume resistivity, surface charge accumulation and flashover under temperature gradient, and finally the ceramic material suitable for long-term insulation support functions in SF6 environments is determined. Summary of the invention
[0005] The object of the present invention is to provide a method for evaluating the performance of ceramic materials for insulation in high-voltage equipment, which is characterized by comprising the following steps:
[0006] Conduct mass loss characteristic evaluation to obtain the mass loss rate of each sample to be tested;
[0007] Use a volume resistivity test device at different temperatures to evaluate the volume resistivity variation with temperature and obtain the surface charge value of each sample to be tested;
[0008] Use the surface charge accumulation test device under temperature gradient to evaluate the surface charge accumulation characteristics under temperature gradient and obtain the material volume resistivity at different temperatures of each test sample;
[0009] Use the surface flashover test device under temperature gradient to evaluate the surface flashover characteristics under temperature gradient and obtain the average surface flashover voltage of each sample to be tested;
[0010] A comprehensive performance evaluation of the test samples was carried out based on the mass loss rate, surface charge value, material volume resistivity at different temperatures and average surface flashover voltage of each test sample.
[0011] The mass loss characteristics evaluation includes:
[0012] Select several cylindrical ceramic samples with the same size and measure the mass of each ceramic sample;
[0013] Each ceramic sample was completely immersed in a hydrofluoric acid solution for a corrosion comparison test. The ceramic samples were corroded at 323K for 1 and 24 hours using 5% and 10% hydrofluoric acid solutions. All samples were polished by the same process. The corroded samples were ultrasonically rinsed in ultrapure water for more than 2 times, with each rinse time of 15 minutes to clean the liquid impurities remaining on the surface. After cleaning, the mass loss rate of each sample after hydrofluoric acid corrosion treatment was counted; the mass loss characteristics of the ceramic material were evaluated by the mass loss rate.
[0014] The volume resistivity test device at different temperatures includes: a high-temperature and high-pressure sealed measurement chamber, a temperature control unit, a high-voltage DC power supply, a weak current measurement system, and a data acquisition device;
[0015] A three-electrode measuring device is provided in the high-temperature and high-pressure sealed measuring chamber, and the three-electrode measuring device includes: a measuring electrode and a high-voltage electrode, and the measuring electrode and the high-voltage electrode clamp and fix the sample to be tested in the high-temperature and high-pressure sealed measuring chamber;
[0016] A heating resistor (4) is provided in the high-temperature and high-pressure sealed measurement cavity, and the heating resistor (4) is connected to a temperature control unit to adjust the internal temperature of the high-temperature and high-pressure sealed measurement cavity;
[0017] The high voltage electrode is connected to a high voltage DC power supply to provide a DC voltage for the three-electrode measuring device;
[0018] The measuring electrode is connected to the data acquisition device through a weak current measurement system to measure the leakage current of the sample to be tested (1); the weak current measurement system is an electrometer; the data acquisition device is provided with a PC acquisition program to calculate the volume resistivity of the sample to be tested at different temperatures based on the leakage current.
[0019] The volume resistivity temperature variation characteristics evaluation includes:
[0020] Step S21: pre-treating the tested sample. Before testing, the tested sample is cleaned and placed in an oven. The upper and lower ends are short-circuited to the ground for discharge treatment to ensure that the tested sample is clean and dry before testing and has no stray charge interference. The tested sample is pre-treated to obtain a pre-treated sheet-shaped tested sample.
[0021] Step S22: the measuring electrode and the high-voltage electrode clamp and fix the pre-treated sheet-shaped sample to be tested in the high-temperature and high-pressure sealed measuring cavity, and seal the high-temperature and high-pressure sealed measuring cavity;
[0022] Step S23: the temperature control unit controls the heating resistor (4) to adjust the temperature inside the high-temperature and high-pressure sealing measurement cavity according to a preset temperature list, wherein the temperature list includes: 20° C., 50° C. and 80° C.;
[0023] Step S24: the high voltage DC power supply applies a DC voltage to the three-electrode measuring device;
[0024] Step S25: the weak current measurement system measures the leakage current of the pre-treated sheet-shaped test sample (1) through an electrometer;
[0025] Step S26: The data acquisition device calculates and obtains the volume resistivity of the material at each temperature in the temperature list of the sample to be tested (1) through the PC acquisition program;
[0026] Step S27: Jump to the step S21 until a preset number of cycles is reached, which is 3 times, and calculate the average volume resistivity at different temperatures obtained from the three tests as the volume resistivity value of the sample to be tested at the temperature.
[0027] The surface charge accumulation test device under temperature gradient comprises: a closed test chamber, an external high-voltage power supply system, a temperature control system, a potential measuring device, and a data storage and processing device;
[0028] A high voltage electrode and a grounding electrode are arranged in the closed test chamber, the high voltage electrode and the grounding electrode clamp and fix the test sample, and the closed test chamber is filled with SF6 gas in the same working condition as the actual working condition;
[0029] The temperature control system is connected to the high voltage electrode and the ground electrode, and applies the same temperature gradient as the actual working condition to the high voltage electrode and the ground electrode;
[0030] An external high-voltage power supply system is connected to the high-voltage electrode and is used to continuously apply a DC voltage to the test sample;
[0031] The potential measuring device includes: a capacitance probe; the capacitance probe is located inside the closed test chamber and is used to measure the surface potential distribution of the test sample;
[0032] The data storage and processing device is used to record the surface potential distribution information of the sample to be tested.
[0033] The evaluation of surface charge accumulation characteristics under temperature gradient includes:
[0034] Step S31: pre-treating the tested sample. Before testing, the tested sample is cleaned and placed in an oven. The upper and lower ends are short-circuited to the ground for discharge treatment to ensure that the tested sample is clean and dry before testing and has no stray charge interference. The tested sample is pre-treated to obtain a pre-treated cylindrical tested sample.
[0035] Step S32: The high voltage electrode and the ground electrode clamp and fix the pre-treated cylindrical test sample in a closed test chamber;
[0036] Step S33: Filling the closed test chamber with SF6 gas in the same working condition as the actual working condition;
[0037] Step S34: the temperature control system applies the same temperature gradient as in actual working conditions to the high voltage electrode and the ground electrode;
[0038] Step S35: before applying voltage, the potential measuring device measures the surface potential distribution of the sample to be tested to obtain the surface potential distribution information of the sample to be tested in the initial state; the data storage and processing device records the surface potential distribution information of the sample to be tested in the initial state;
[0039] Step S36: The high voltage electrode and the ground electrode continuously apply a DC voltage to the test sample for 2 hours;
[0040] Step S37: After the pressure is released, the potential measuring device measures the surface potential distribution of the sample to be tested again to obtain the surface potential distribution information of the sample to be tested in the actual state; the data storage and processing device records the surface potential distribution information of the sample to be tested in the actual state.
[0041] Step S38: The data storage and processing device makes a difference between the measured value of the surface potential distribution information of the test sample in the actual state and the measured value of the surface potential distribution information of the test sample in the initial state, and obtains the corresponding surface charge value according to the product of the calibration coefficient and the surface potential data, so as to evaluate the surface charge accumulation performance of the test sample under the combined action of the electric field-temperature gradient.
[0042] The surface flashover test device under temperature gradient comprises: a flat plate electrode, a closed test cavity, a high voltage DC power generator, and a measuring and protecting voltage dividing resistor;
[0043] The flat plate electrode is located inside the closed test chamber, and the flat plate electrode includes: a high voltage electrode and a grounding electrode; the high voltage electrode and the grounding electrode clamp and fix the test sample, and the closed test chamber is filled with SF6 gas under the same working conditions as the actual working conditions;
[0044] The temperature control system is connected to the high voltage electrode and the ground electrode, and applies the same temperature gradient as the actual working condition to the high voltage electrode and the ground electrode;
[0045] The high-voltage DC power generator includes: a power buck-boost control console, a rectifier, a transformer, and a high-voltage AC power supply, which is used to continuously apply a DC voltage to the test sample;
[0046] Measuring and protecting voltage-dividing resistors, including: protection resistors and voltage-dividing resistors, used to protect circuits from overload and measure voltage values;
[0047] The high-voltage DC power generator cooperates with the measuring and protecting voltage-dividing resistor to realize the slow voltage-boosting method until flashover occurs, and the flashover voltage value is recorded from the power supply step-up and step-down console.
[0048] The surface flashover characteristics evaluation under the temperature gradient includes:
[0049] Step S41: pre-treating the tested sample. Before testing, the tested sample is cleaned and placed in an oven. The upper and lower ends are short-circuited to the ground for discharge treatment to ensure that the tested sample is clean and dry before testing and has no stray charge interference. The tested sample is pre-treated to obtain a pre-treated cylindrical tested sample.
[0050] Step S42: The high voltage electrode and the ground electrode clamp and fix the pre-treated cylindrical test sample in the closed test chamber, and keep the high voltage electrode and the ground electrode in close contact with the upper and lower surfaces of the cylindrical test sample;
[0051] Step S43: Filling the closed test chamber with SF6 gas in the same working condition as the actual working condition;
[0052] Step S44: the temperature control system applies the same temperature gradient as in actual working conditions to the high voltage electrode and the ground electrode;
[0053] Step S45: The high-voltage DC power generator cooperates with the measuring and protecting voltage-dividing resistor, and uses a slow voltage-raising method until a flashover occurs, and the flashover voltage value is recorded;
[0054] Step S46: evacuate the SF6 gas after discharge in the sealed test chamber with a vacuum pump, and then refill it with clean SF6 gas;
[0055] Step S47: Jump to the step S41, until the preset number of cycles is reached, obtain the average value of the flashover voltage, and evaluate the surface flashover performance of the ceramic material under the temperature gradient through the average value of the flashover voltage.
[0056] The beneficial effects of the present invention are:
[0057] The method for evaluating the performance of ceramic materials for insulation in high-voltage equipment described in the present invention evaluates the comprehensive performance of ceramic materials by focusing on mass loss, volume resistivity change with temperature, surface charge accumulation under temperature gradient, and surface flashover under temperature gradient, and specifically includes the following advantages:
[0058] (1) Using hydrofluoric acid to conduct corrosion tests on ceramic materials can effectively simulate the hydrofluoric acid environment produced by the combination of HF generated by the decomposition of SF6 due to partial discharge and trace moisture in the internal insulation environment. By analyzing the mass loss rate, the acid corrosion resistance of the ceramic materials used for internal insulation can be intuitively reflected.
[0059] (2) When measuring volume resistivity, this method measures the volume resistivity of ceramic materials under different temperatures, which can comprehensively explore the temperature stability of the volume resistivity of ceramic materials, so as to facilitate the evaluation of the performance of ceramics used in insulation scenarios in high-voltage equipment.
[0060] (3) When measuring the surface charge value and surface flashover voltage, high and low voltage electrodes are applied with high and low temperatures respectively, so that a temperature gradient is generated in the ceramic sample. This simulates the temperature gradient formed between the supporting insulator and the outer casing due to the heat generated by the operation of the guide rod in the internal insulation environment. The surface charge value and surface flashover voltage measured under the temperature gradient are used to evaluate the surface charge accumulation performance and surface flashover performance of the ceramic material, and a performance evaluation method that conforms to actual operating conditions is proposed. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 A schematic diagram of a flow chart of a method for evaluating the performance of ceramic materials for insulation in high-voltage equipment disclosed in the present invention;
[0062] Figure 2 It is a schematic diagram of the structure of a volume resistivity test device at different temperatures according to an embodiment of the present invention;
[0063] Figure 3 It is a schematic structural diagram of a surface charge accumulation test device under temperature gradient according to an embodiment of the present invention;
[0064] Figure 4 It is a schematic structural diagram of a surface flashover test device under temperature gradient according to an embodiment of the present invention;
[0065] Among them, 1-sample to be tested, 2-measuring electrode, 3-high voltage electrode, 4-heating resistor, 5-weak current measurement system, 6-data acquisition device, 7-high voltage DC power supply, 8-temperature control system, 9-grounding electrode, 10-potential measurement device, 11-data storage and processing device, 12-protection resistor, 13-voltage dividing resistor, 14-high voltage DC power generator, 15-high temperature and high pressure sealed measurement chamber, 16-sealed test chamber, 17-external high voltage power supply system. DETAILED DESCRIPTION
[0066] The present invention provides a method for evaluating the performance of ceramic materials used for insulation in high-voltage equipment. The present invention is further described in detail below in conjunction with the accompanying drawings.
[0067] like Figure 1 The embodiment of the present invention shown discloses a method for evaluating the performance of ceramic materials used for insulation in high-voltage equipment, comprising the following steps:
[0068] Performing mass loss characteristic evaluation to obtain the mass loss rate of each test sample 1;
[0069] Using a volume resistivity test device at different temperatures, the volume resistivity is evaluated with temperature, and the surface charge value of each test sample 1 is obtained;
[0070] Using a surface charge accumulation test device under temperature gradient, the surface charge accumulation characteristics under temperature gradient are evaluated to obtain the material volume resistivity of each test sample 1 at different temperatures;
[0071] Using a surface flashover test device under temperature gradient, the surface flashover characteristics under temperature gradient are evaluated, and the average value of the surface flashover voltage of each test sample 1 is obtained;
[0072] A comprehensive performance evaluation of the test samples 1 is performed based on the mass loss rate, surface charge value, material volume resistivity at different temperatures and average surface flashover voltage of each test sample 1.
[0073] In this embodiment, a performance evaluation method for ceramic materials used for internal insulating supports of high-voltage gas-insulated equipment is disclosed, including: comprehensive evaluation of four material properties: mass loss, volume resistivity change with temperature, surface charge accumulation under temperature gradient, and surface flashover under temperature gradient. Among them, mass loss refers to the acid corrosion resistance of the material. Different ceramic materials are corroded with hydrofluoric acid solution, and the mass loss rate of the material after corrosion is statistically calculated to evaluate its corrosion resistance in the internal insulation environment. In the internal insulation environment, the heat generated by the guide rod during operation causes the insulating support to form a temperature gradient distribution, which significantly affects the surface charge accumulation, and then affects the surface electric field distribution, causing the surface electric field of the insulating support to be distorted, and then causing the surface flashover voltage to decrease. Therefore, the volume resistivity, surface charge accumulation and surface flashover characteristics of the material under the temperature gradient are evaluated. Volume resistivity changes with temperature: voltage is applied to the ceramic material at different temperatures, the leakage current is measured and the volume resistivity is calculated to evaluate the volume resistivity change characteristics of each material with temperature. Surface charge accumulation under temperature gradient: The ceramic material for the test is placed between two electrodes, and a temperature gradient consistent with the actual working conditions is applied to the electrodes. A voltage value calculated by the electric field equivalent method is applied, and the surface potential of the material is measured with an electrostatic capacitance probe. The surface charge accumulation characteristics of the tested sample under the combined action of the electric field and temperature gradient are obtained through the inversion algorithm. Surface flashover under temperature gradient: SF6 gas is filled in the closed test chamber 16, and a temperature gradient consistent with the actual working conditions is applied to the electrodes on both sides. The voltage is increased by a slow voltage increase method until a flashover occurs, and the flashover voltage is measured to evaluate the surface flashover characteristics of the material under the temperature gradient.
[0074] Therefore, the performance evaluation method for ceramic materials used for insulation in high-voltage equipment described in this embodiment evaluates the performance of ceramic materials used for insulation supports in high-voltage gas-insulated equipment, and obtains the mass loss rate, volume resistivity temperature stability, surface charge value under temperature gradient, and flashover voltage of each material after hydrofluoric acid corrosion. The test samples are various ceramic materials. By comparing the performance data of each ceramic material, the performance of each ceramic material is evaluated, and ceramic materials with better performance are selected for the design and manufacture of insulation supports in high-voltage gas-insulated equipment.
[0075] The following describes the steps of the method for evaluating the performance of ceramic materials used for insulation in high-voltage equipment.
[0076] 1. Evaluate the mass loss characteristics and obtain the mass loss rate of each test sample 1;
[0077] The mass loss characteristics evaluation includes:
[0078] Select several cylindrical ceramic samples with the same size and measure the mass of each ceramic sample;
[0079] Each ceramic sample was completely immersed in a hydrofluoric acid solution for a corrosion comparison test. The ceramic samples were corroded at 323K for 1 and 24 hours using 5% and 10% hydrofluoric acid solutions. All samples were polished by the same process. The corroded samples were ultrasonically rinsed in ultrapure water for more than 2 times, with each rinse time of 15 minutes to clean the liquid impurities remaining on the surface. After cleaning, the mass loss rate of each sample after hydrofluoric acid corrosion treatment was counted; the mass loss characteristics of the ceramic material were evaluated by the mass loss rate.
[0080] In this embodiment, a corrosion comparison test is carried out on cylindrical ceramic samples of the same size using 5% and 10% concentration hydrofluoric acid solutions. After the test, the liquid impurities remaining on the surface of the sample are cleaned off, and the mass of the sample after corrosion is measured to obtain the mass loss rate. The mass loss rate is used to evaluate the mass loss performance of the ceramic material.
[0081] 2. Using a volume resistivity test device at different temperatures, evaluate the volume resistivity variation with temperature and obtain the surface charge value of each test sample 1;
[0082] like Figure 2 As shown, the volume resistivity test device at different temperatures includes: a high-temperature and high-pressure sealed measurement chamber 15, a temperature control unit, a high-voltage DC power supply 7, a weak current measurement system 5 and a data acquisition device 6;
[0083] A three-electrode measuring device is provided in the high-temperature and high-pressure sealed measuring cavity 15, and the three-electrode measuring device includes: a measuring electrode 2 and a high-voltage electrode 3, and the measuring electrode 2 and the high-voltage electrode 3 clamp and fix the sample 1 to be tested in the high-temperature and high-pressure sealed measuring cavity 15;
[0084] A heating resistor 4 is provided in the high-temperature and high-pressure sealed measurement cavity 15, and the heating resistor 4 is connected to a temperature control unit to adjust the internal temperature of the high-temperature and high-pressure sealed measurement cavity 15;
[0085] The high voltage electrode 3 is connected to a high voltage DC power supply 7 to provide a DC voltage for the three-electrode measuring device;
[0086] The measuring electrode 2 is connected to the data acquisition device 6 through a weak current measurement system 5 to measure the leakage current of the test sample 1; the weak current measurement system 5 is an electrometer; the data acquisition device 6 is provided with a PC acquisition program to calculate the volume resistivity of the test sample 1 at different temperatures based on the leakage current.
[0087] The volume resistivity temperature variation characteristics evaluation includes:
[0088] Step S21: pre-treating the tested sample. Before testing, the tested sample is cleaned and placed in an oven. The upper and lower ends are short-circuited to the ground for discharge treatment to ensure that the tested sample is clean and dry before testing and has no stray charge interference. The tested sample 1 is pre-treated to obtain a pre-treated sheet-shaped tested sample.
[0089] Step S22: the measuring electrode 2 and the high-voltage electrode 3 clamp and fix the pre-treated sheet-shaped test sample in the high-temperature and high-pressure sealed measuring cavity 15, and seal the high-temperature and high-pressure sealed measuring cavity 15;
[0090] Step S23: the temperature control unit controls the heating resistor 4 to adjust the internal temperature of the high-temperature and high-pressure sealing measurement cavity 15 according to a preset temperature list, wherein the temperature list includes: 20° C., 50° C. and 80° C.;
[0091] Step S24: the high voltage DC power supply 7 applies a DC voltage to the three-electrode measuring device;
[0092] Step S25: the weak current measurement system 5 measures the leakage current of the pre-treated sheet-shaped test sample through an electrometer;
[0093] Step S26: The data acquisition device 6 calculates and obtains the volume resistivity of the material at each temperature in the temperature list of the test sample 1 through the PC acquisition program;
[0094] Step S27: Jump to step S21 until a preset number of cycles is reached, which is 3 times, and calculate the average volume resistivity at different temperatures obtained from three tests as the volume resistivity value of the test sample 1 at the temperature.
[0095] In this embodiment, the volume resistivity test device at different temperatures includes: a high temperature and high pressure sealed measurement chamber 15, a temperature control unit, a high voltage DC power supply 7, a weak current measurement system 5 and a data acquisition device 6, which constitute a material resistivity test platform at different temperatures. The pretreated sheet ceramic sample is placed in the measurement chamber, the sample is clamped and fixed by three electrodes, the measurement chamber is sealed, and the temperature inside the experimental chamber is 20°C, 50°C and 80°C, respectively. A DC voltage is applied, and the leakage current of the ceramic sample is measured. The volume resistivity of the ceramic material at different temperatures is calculated, and each group of experiments is repeated three times to eliminate the influence of accidental errors. The volume resistivity of the material at different temperatures is used to evaluate the temperature stability of the volume resistance of the ceramic material.
[0096] 3. Using a surface charge accumulation test device under temperature gradient, evaluate the surface charge accumulation characteristics under temperature gradient, and obtain the material volume resistivity of each test sample 1 at different temperatures;
[0097] like Figure 3As shown, the surface charge accumulation test device under temperature gradient comprises: a closed test chamber 16, an external high voltage power supply system 17, a temperature control system 8, a potential measuring device 10, and a data storage and processing device 11;
[0098] A high voltage electrode 3 and a grounding electrode 9 are provided in the closed test chamber 16, and the high voltage electrode 3 and the grounding electrode 9 clamp and fix the test sample 1, and the closed test chamber 16 is filled with SF6 gas in the same working condition as the actual working condition;
[0099] The temperature control system 8 is connected to the high voltage electrode 3 and the ground electrode 9, and applies the same temperature gradient as the actual working condition to the high voltage electrode 3 and the ground electrode 9;
[0100] The external high-voltage power supply system 17 is connected to the high-voltage electrode 3 and is used to continuously apply a DC voltage to the test sample 1;
[0101] The potential measuring device 10 comprises: a capacitance probe; the capacitance probe is located inside the closed test chamber 16 and is used to measure the surface potential distribution of the test sample 1;
[0102] The data storage and processing device 11 is used to record the surface potential distribution information of the sample to be tested.
[0103] In this embodiment, the data storage and processing device 11 is an oscilloscope.
[0104] The evaluation of surface charge accumulation characteristics under temperature gradient includes:
[0105] Step S31: pre-treat the tested sample. Before testing, the tested sample is cleaned and placed in an oven. The upper and lower ends are short-circuited to the ground for discharge treatment to ensure that the tested sample is clean and dry before testing and has no stray charge interference. Pre-treat the tested sample 1 to obtain a pre-treated cylindrical tested sample.
[0106] Step S32: The high voltage electrode 3 and the ground electrode 9 clamp and fix the pre-treated cylindrical test sample in the closed test chamber 16;
[0107] Step S33: Filling the sealed test chamber 16 with SF6 gas in the same working condition as the actual working condition;
[0108] Step S34: the temperature control system 8 applies the same temperature gradient as in the actual working condition to the high voltage electrode 3 and the ground electrode 9;
[0109] Step S35: before applying voltage, the potential measuring device 10 measures the surface potential distribution of the sample to be tested to obtain the surface potential distribution information of the sample to be tested in the initial state; the data storage and processing device 11 records the surface potential distribution information of the sample to be tested in the initial state;
[0110] Step S36: the high voltage electrode 3 and the ground electrode 9 continuously apply a DC voltage to the test sample 1 for 2 hours;
[0111] Step S37: After the pressure is released, the potential measuring device 10 measures the surface potential distribution of the test sample 1 again to obtain the surface potential distribution information of the test sample in the actual state; the data storage and processing device 11 records the surface potential distribution information of the test sample in the actual state.
[0112] Step S38: The data storage and processing device 11 subtracts the measured value of the surface potential distribution information of the test sample in the actual state from the measured value of the surface potential distribution information of the test sample in the initial state, and obtains the corresponding surface charge value based on the product of the calibration coefficient and the surface potential data, so as to evaluate the surface charge accumulation performance of the test sample 1 under the combined action of the electric field-temperature gradient.
[0113] In this embodiment, the surface charge accumulation test device under the temperature gradient includes: a closed test chamber 16, an external high-voltage power supply system 17, a temperature control system 8, an insulating device, a potential measuring device 10, and a data storage and processing device 11. A passive electrostatic capacitance surface charge measurement platform is formed. The experiment uses a pretreated cylindrical ceramic sample. The inside of the experimental chamber is filled with SF6 gas with the same working conditions as the actual working conditions, and the high-voltage electrode 3 and the grounding electrode 9 are applied with the same temperature gradient as the actual working conditions. Before applying the voltage, the surface potential distribution of the sample in the initial state is measured, and the DC voltage is continuously applied for 2h. After the pressure is removed, the surface potential of the sample is measured and recorded. After obtaining the measured data of the surface potential, it is subtracted from the measured value of the initial state, and the corresponding surface charge value can be obtained according to the product of the calibration coefficient and the surface potential data to evaluate the surface charge accumulation performance of the ceramic material under the combined action of the electric field-temperature gradient.
[0114] 4. Use the surface flashover test device under temperature gradient to evaluate the surface flashover characteristics under temperature gradient, and obtain the average value of the surface flashover voltage of each test sample 1;
[0115] like Figure 4 As shown, the surface flashover test device under temperature gradient includes: a flat electrode, a closed test chamber 16, a high-voltage DC power generator 14, and a measuring and protecting voltage-dividing resistor;
[0116] The flat plate electrode is located inside the closed test chamber 16, and the flat plate electrode includes: a high voltage electrode 3 and a ground electrode 9; the high voltage electrode 3 and the ground electrode 9 clamp and fix the test sample 1, and the closed test chamber 16 is filled with SF6 gas in the same working condition as the actual working condition;
[0117] The temperature control system 8 is connected to the high voltage electrode 3 and the ground electrode 9, and applies the same temperature gradient as the actual working condition to the high voltage electrode 3 and the ground electrode 9;
[0118] The high-voltage DC power generator 14 includes: a power buck-boost control console, a rectifier, a transformer, and a high-voltage AC power supply, and is used to continuously apply a DC voltage to the test sample 1;
[0119] Measuring and protecting the voltage-dividing resistor, including: a protection resistor 12 and a voltage-dividing resistor 13, used to protect the circuit from overload and measure the voltage value;
[0120] The high voltage DC power generator 14 cooperates with the measuring and protecting voltage divider resistor to realize the flashover by the slow voltage boost method, and the flashover voltage value is recorded from the power boost and buck console.
[0121] The surface flashover characteristics evaluation under the temperature gradient includes:
[0122] Step S41: pre-treating the tested sample. Before testing, the tested sample is cleaned and placed in an oven. The upper and lower ends are short-circuited to the ground for discharge treatment to ensure that the tested sample is clean and dry before testing and has no stray charge interference. The tested sample 1 is pre-treated to obtain a pre-treated cylindrical tested sample.
[0123] Step S42: The high voltage electrode 3 and the ground electrode 9 clamp and fix the pre-treated cylindrical test sample in the closed test chamber 16, and keep the high voltage electrode 3 and the ground electrode 9 in close contact with the upper and lower surfaces of the cylindrical test sample;
[0124] Step S43: Filling the closed test chamber 16 with SF6 gas in the same working condition as the actual working condition;
[0125] Step S44: the temperature control system 8 applies the same temperature gradient as the actual working condition to the high voltage electrode 3 and the ground electrode 9;
[0126] Step S45: The high-voltage DC power generator 14 cooperates with the measuring and protecting voltage-dividing resistor to use a slow voltage-raising method until a flashover occurs, and the flashover voltage value is recorded;
[0127] Step S46: evacuate the SF6 gas after discharge in the sealed test chamber 16 with a vacuum pump, and then refill it with clean SF6 gas;
[0128] Step S47: Jump to the step S41, until the preset number of cycles is reached, obtain the average value of the flashover voltage, and evaluate the surface flashover performance of the ceramic material under the temperature gradient through the average value of the flashover voltage.
[0129] In this embodiment, the surface flashover test device under temperature gradient includes: a flat electrode, a closed test cavity 16, a high-voltage DC power generator 14, and a measuring and protecting voltage-dividing resistor; forming a DC surface flashover voltage test experimental platform under temperature gradient. Place the cylindrical ceramic sample pretreated before the experiment inside the cavity, keep the two metal electrodes in close contact with the sample to be tested, and the metal electrodes have the same temperature gradient as the actual working condition. Fill with SF6 gas at the pressure under actual working conditions. Slowly increase the pressure until flashover occurs, record the voltage of the boost control cabinet before flashover, record the flashover voltage value, replace the SF6 gas after flashover occurs, repeat the experiment many times, obtain the average value of the surface flashover voltage, and use the average value of the surface flashover voltage to evaluate the surface flashover performance of the ceramic material under temperature gradient.
[0130] 5. Comprehensive performance evaluation is performed on the test samples 1 according to the mass loss rate, surface charge value, material volume resistivity at different temperatures and average surface flashover voltage of each test sample 1.
[0131] In summary, most of the insulating ceramic performance evaluation methods in the prior art are screening and evaluation under external insulation conditions, and are not applicable to the internal insulation working conditions of high-voltage equipment. The SF6 gas inside the high-voltage equipment will decompose HF under local discharge, and there is trace water inside the equipment during actual operation, so HF will form hydrofluoric acid to corrode the supporting insulators. As the operating time increases, the internal insulation environment will become more and more complex. The heat generated during operation will cause uneven heating of the supporting insulators, causing a temperature gradient in the supporting insulators, which will in turn affect its volume resistivity, and the volume resistivity will affect surface charge accumulation and flashover. Therefore, hydrofluoric acid corrosion and temperature gradients in internal insulation conditions cannot be ignored.
[0132] On this basis, the present invention proposes a new ceramic material performance evaluation method that takes into account the above-mentioned internal insulation characteristics. The application of the ceramic material performance evaluation method for high-voltage equipment internal insulation disclosed in the present invention can achieve:
[0133] ●Achieved the performance evaluation of ceramic material mass loss;
[0134] ●Achieved the temperature stability evaluation of the resistivity of ceramic materials;
[0135] ●Achieved the evaluation of surface charge accumulation characteristics of ceramic materials under the combined action of electric field and temperature gradient;
[0136] Realized the evaluation of surface flashover performance of ceramic materials under temperature gradient;
[0137] ●Realized the performance evaluation test of ceramic insulation materials under special insulation conditions in high-voltage equipment.
[0138] Through comprehensive evaluation of the performance of ceramic materials for internal insulation, it is convenient to find a high-performance ceramic insulation material formulation system in combination with actual working conditions. From the wide variety of high-performance ceramic material formulation systems with very different insulation properties, a ceramic basic material system with high surface insulation strength and strong compatibility with SF6 gas is selected. A comprehensive performance evaluation is conducted on the material's corrosion resistance, temperature stability of volume resistivity, surface charge accumulation and flashover under temperature gradient, and finally the ceramic material suitable for long-term insulation support functions in SF6 environment is determined.
Claims
1. A method for evaluating the performance of ceramic materials for insulation in high-voltage equipment, characterized in that: The steps include: Performing mass loss characteristic evaluation to obtain the mass loss rate of each test sample (1); Using a volume resistivity test device at different temperatures, the volume resistivity is evaluated as a function of temperature, and the surface charge value of each sample to be tested (1) is obtained; Using a surface charge accumulation test device under temperature gradient, evaluating the surface charge accumulation characteristics under temperature gradient, and obtaining the material volume resistivity of each test sample (1) at different temperatures; Using a surface flashover test device under temperature gradient, evaluating the surface flashover characteristics under temperature gradient, and obtaining the average surface flashover voltage of each test sample (1); A comprehensive performance evaluation is performed on the test samples (1) based on the mass loss rate, surface charge value, material volume resistivity at different temperatures and average surface flashover voltage of each test sample (1).
2. The method for evaluating the performance of ceramic materials for insulation in high-voltage equipment according to claim 1, characterized in that: The mass loss characteristics evaluation includes: Select several cylindrical ceramic samples with the same size and measure the mass of each ceramic sample; Each ceramic sample was completely immersed in a hydrofluoric acid solution for a corrosion comparison test. The ceramic samples were corroded at 323K for 1 and 24 hours using 5% and 10% hydrofluoric acid solutions. All samples were polished by the same process. The corroded samples were ultrasonically rinsed in ultrapure water for more than 2 times, with each rinse time of 15 minutes to clean the liquid impurities remaining on the surface. After cleaning, the mass loss rate of each sample after hydrofluoric acid corrosion treatment was counted; the mass loss characteristics of the ceramic material were evaluated by the mass loss rate.
3. The method for evaluating the performance of ceramic materials for insulation in high-voltage equipment according to claim 1, characterized in that: The volume resistivity test device at different temperatures comprises: a high-temperature and high-pressure sealed measurement chamber (15), a temperature control unit (not shown in the figure), a high-voltage direct current power supply (7), a weak current measurement system (5) and a data acquisition device (6); A three-electrode measuring device is provided in the high-temperature and high-pressure sealed measuring cavity (15), and the three-electrode measuring device comprises: a measuring electrode (2) and a high-voltage electrode (3), and the measuring electrode (2) and the high-voltage electrode (3) clamp and fix the sample to be tested (1) in the high-temperature and high-pressure sealed measuring cavity (15); A heating resistor (4) is provided in the high-temperature and high-pressure sealed measurement cavity (15), and the heating resistor (4) is connected to a temperature control unit to adjust the internal temperature of the high-temperature and high-pressure sealed measurement cavity (15); The high voltage electrode (3) is connected to a high voltage DC power supply (7) to provide a DC voltage for the three-electrode measuring device; The measuring electrode (2) is connected to the data acquisition device (6) via a weak current measurement system (5) to measure the leakage current of the sample to be tested (1); the weak current measurement system (5) is an electrometer; the data acquisition device (6) is provided with a PC acquisition program to calculate the volume resistivity of the sample to be tested (1) at different temperatures based on the leakage current.
4. The method for evaluating the performance of ceramic materials for insulation in high-voltage equipment according to claim 1, characterized in that: The volume resistivity temperature variation characteristics evaluation includes: Step S21: pre-treat the tested sample. Before testing, the tested sample is cleaned and placed in an oven. The upper and lower ends are short-circuited to the ground for discharge treatment to ensure that the tested sample is clean, dry and free of stray charge interference before testing. The tested sample is pre-treated (1) to obtain a pre-treated sheet-shaped tested sample. Step S22: the measuring electrode (2) and the high-voltage electrode (3) clamp and fix the pre-treated sheet-shaped sample to be tested in the high-temperature and high-pressure sealed measuring cavity (15), and seal the high-temperature and high-pressure sealed measuring cavity (15); Step S23: the temperature control unit controls the heating resistor (4) to adjust the internal temperature of the high temperature and high pressure sealed measurement cavity (15) according to a preset temperature list, wherein the temperature list includes: 20° C., 50° C. and 80° C.; Step S24: the high voltage DC power supply (7) applies a DC voltage to the three-electrode measuring device; Step S25: the weak current measurement system (5) measures the leakage current of the pre-treated sheet-shaped test sample through an electrometer; Step S26: The data acquisition device (6) calculates and obtains the volume resistivity of the material at each temperature in the temperature list of the sample to be tested (1) through the PC acquisition program; Step S27: Jump to step S21 until a preset number of cycles is reached, which is 3 times, and calculate the average volume resistivity at different temperatures obtained from three tests as the volume resistivity value of the sample (1) to be tested at that temperature.
5. The method for evaluating the performance of ceramic materials for insulation in high-voltage equipment according to claim 1, characterized in that: The surface charge accumulation test device under temperature gradient comprises: a sealed test chamber (16), an external high-voltage power supply system (17), a temperature control system (8), a potential measuring device (10), and a data storage and processing device (11); A high voltage electrode (3) and a grounding electrode (9) are arranged in the sealed test chamber (16), the high voltage electrode (3) and the grounding electrode (9) clamp and fix the test sample (1), and the sealed test chamber (16) is filled with SF6 gas in the same working condition as the actual working condition; The temperature control system (8) is connected to the high voltage electrode (3) and the ground electrode (9), and applies a temperature gradient identical to that in actual working conditions to the high voltage electrode (3) and the ground electrode (9); An external high-voltage power supply system (17) is connected to the high-voltage electrode (3) and is used to continuously apply a DC voltage to the test sample (1); The potential measuring device (10) comprises: a capacitance probe; the capacitance probe is located inside a closed test chamber (16) and is used to measure the surface potential distribution of a test sample (1); The data storage and processing device (11) is used to record the surface potential distribution information of the sample to be tested (1).
6. The method for evaluating the performance of ceramic materials for insulation in high-voltage equipment according to claim 1, characterized in that: The evaluation of surface charge accumulation characteristics under temperature gradient includes: Step S31: pre-treat the test sample. Before testing, the test sample is cleaned and placed in an oven. The upper and lower ends are short-circuited to the ground for discharge treatment to ensure that the test sample is clean, dry and free of stray charge interference before testing. Pre-treat the test sample (1) to obtain a pre-treated cylindrical test sample. Step S32: The high voltage electrode (3) and the ground electrode (9) clamp and fix the pre-treated cylindrical test sample in the sealed test chamber (16); Step S33: filling the sealed test chamber (16) with SF6 gas in the same working condition as the actual working condition; Step S34: the temperature control system (8) applies a temperature gradient identical to that in actual working conditions to the high voltage electrode (3) and the ground electrode (9); Step S35: before applying voltage, the potential measuring device (10) measures the surface potential distribution of the test sample (1) to obtain the surface potential distribution information of the test sample in the initial state; the data storage and processing device (11) records the surface potential distribution information of the test sample in the initial state; Step S36: The high voltage electrode (3) and the ground electrode (9) continuously apply a DC voltage to the test sample (1) for 2 hours; Step S37: After the pressure is released, the potential measuring device (10) measures the surface potential distribution of the sample to be tested (1) again to obtain the surface potential distribution information of the sample to be tested in the actual state; the data storage and processing device (11) records the surface potential distribution information of the sample to be tested in the actual state. Step S38: The data storage and processing device (11) makes a difference between the measured value of the surface potential distribution information of the test sample in the actual state and the measured value of the surface potential distribution information of the test sample in the initial state, and obtains the corresponding surface charge value according to the product of the calibration coefficient and the surface potential data, so as to evaluate the surface charge accumulation performance of the test sample (1) under the combined action of the electric field-temperature gradient.
7. The method for evaluating the performance of ceramic materials for insulation in high-voltage equipment according to claim 1, characterized in that: The surface flashover test device under temperature gradient comprises: a flat plate electrode, a sealed test cavity (16), a high-voltage direct current power generator (14), and a measuring and protecting voltage-dividing resistor; The flat plate electrode is located inside the sealed test chamber (16), and comprises: a high-voltage electrode (3) and a grounding electrode (9); the high-voltage electrode (3) and the grounding electrode (9) clamp and fix the sample to be tested (1), and the sealed test chamber (16) is filled with SF6 gas in the same working condition as the actual working condition; The temperature control system (8) is connected to the high voltage electrode (3) and the ground electrode (9), and applies a temperature gradient identical to that in actual working conditions to the high voltage electrode (3) and the ground electrode (9); The high-voltage DC power generator (14) comprises: a power step-up and step-down control console, a rectifier, a transformer and a high-voltage AC power source, and is used to continuously apply a DC voltage to the test sample (1); The measuring and protecting voltage-dividing resistor comprises: a protecting resistor (12) and a voltage-dividing resistor (13), which are used to protect the circuit from overload and measure the voltage value; A high-voltage direct current power generator (14) cooperates with a measuring and protecting voltage-dividing resistor to achieve a slow voltage-raising method until a flashover occurs, and the flashover voltage value is recorded on a power supply voltage-raising and voltage-lowering console.
8. The method for evaluating the performance of ceramic materials for insulation in high-voltage equipment according to claim 1, characterized in that: The surface flashover characteristics evaluation under the temperature gradient includes: Step S41: pre-treat the tested sample. Before testing, the tested sample is cleaned and placed in an oven. The upper and lower ends are short-circuited to the ground for discharge treatment to ensure that the tested sample is clean, dry and free of stray charge interference before testing. Pre-treat the tested sample (1) to obtain a pre-treated cylindrical tested sample. Step S42: The high voltage electrode (3) and the ground electrode (9) clamp and fix the pre-treated cylindrical test sample in the closed test chamber (16), and keep the high voltage electrode (3) and the ground electrode (9) in close contact with the upper and lower surfaces of the cylindrical test sample; Step S43: Filling the sealed test chamber (16) with SF6 gas in the same working condition as the actual working condition; Step S44: the temperature control system (8) applies a temperature gradient identical to that in actual working conditions to the high voltage electrode (3) and the ground electrode (9); Step S45: The high voltage DC power generator (14) cooperates with the measuring and protecting voltage divider resistor to use a slow voltage boost method until a flashover occurs, and the flashover voltage value is recorded; Step S46: evacuating the SF6 gas after discharge in the sealed test chamber (16) with a vacuum pump, and then refilling it with clean SF6 gas; Step S47: Jump to the step S41, until the preset number of cycles is reached, obtain the average value of the flashover voltage, and evaluate the surface flashover performance of the ceramic material under the temperature gradient through the average value of the flashover voltage.
Citation Information
Patent Citations
Fatigue test device and method for solid insulation degradation process
CN103823166A
Device and method for measuring quantity of electric charges on surface of basin-type insulator under temperature gradient field
CN108445309A
Insulator charge and flashover test device and method under electrothermal composite field
CN113608085A
Epoxy resin surface flashover test device
CN116679178A
High-temperature-resistant and chemical-corrosion-resistant insulating paint, enameled wire and preparation method
CN118421191A